Distribution and availability of mercury and methylmercury in different waters from the Rio Madeira Basin, Amazon - Vieira, Miguel; Bernardi, José V.E.; Dórea, José G.; Rocha, Bruno C.P. [UNESP]; Ribeiro, Romulo; Zara, Luis F. (Elsevier, 2018)
Waters from the Amazon Basin have distinct physicochemical characteristics that can be optically classified as “black”, “clear” and “white”. We studied the distribution of total-Hg (THg) and methyl-Hg (MeHg) in these waters and respective suspended solids, sediment, phytoplankton, zooplankton, and benthic macroinvertebrates (BM) in the Madeira River Basin. Compared with the other types of water, the more acidic “black” kind had the highest THg and MeHg concentrations. The trend (black > clear > white) occurred for the concentrations of THg and MeHg in sediments and in the biotic compartment (plankton, macroinvertebrates). Organic Hg accounted for a small percentage (0.6–0.4%) of the THg in sediments but was highest in water (17–15%). For plankton and BM, the biota sediment accumulation factor (BSAFs) of MeHg (53–125) were greater than those of THg (4.5–15); however, the BSAF trend according to water type (black > clear > white) was only significant for MeHg. Sediment THg is correlated with all forms of Hg in biotic and abiotic matrices. The results indicate that water acidity in the Amazon is an important chemical characteristic in assessing Hg contamination of sediments and bioaccumulation in the aquatic food web. The differences in the BSAFs between THg and MeHg support the use of this factor for evaluating the bioaccumulation potential of sediment-bound Hg. The results add information critical to assessing environmental and health risks related to Hg methylation and potential fish-MeHg contamination, especially in tropical aquatic environments.
Keywords: Amazon; Mercury; Methylmercury; pH; Plankton; Sediments; Water color